2017
DOI: 10.1186/s12974-017-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Sac-1004, a vascular leakage blocker, reduces cerebral ischemia—reperfusion injury by suppressing blood–brain barrier disruption and inflammation

Abstract: BackgroundBlood–brain barrier (BBB) breakdown and inflammation are critical events in ischemic stroke, contributing to aggravated brain damage. The BBB mainly consists of microvascular endothelial cells sealed by tight junctions to protect the brain from blood-borne substances. Thus, the maintenance of BBB integrity may be a potential target for neuroprotection. Sac-1004, a pseudo-sugar derivative of cholesterol, enhances the endothelial barrier by the stabilization of the cortical actin ring.ResultsHere, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 70 publications
2
77
0
Order By: Relevance
“…Another promising pharmacological approach targeting BBB breakdown is Sac-1004, a pseudo-sugar derivative of cholesterol, which enhances endothelial barrier by stabilizing the cortical actin ring. Sac-1004 suppressed IL-1β-induced monolayer hyperpermeability of human brain microvascular endothelial cell loss of tight junctions, and expression of adhesion molecules and activation of NF-κΒ (Zhang et al, 2017). In a rat model of acute transient cerebral ischemia, Sac-1004 reduced BBB leakage and loss of tight junction proteins, inhibited glial activation, and ameliorated neurological deficits and ischemic damage (Zhang et al, 2017).…”
Section: Emerging Pharmacological Approachesmentioning
confidence: 99%
“…Another promising pharmacological approach targeting BBB breakdown is Sac-1004, a pseudo-sugar derivative of cholesterol, which enhances endothelial barrier by stabilizing the cortical actin ring. Sac-1004 suppressed IL-1β-induced monolayer hyperpermeability of human brain microvascular endothelial cell loss of tight junctions, and expression of adhesion molecules and activation of NF-κΒ (Zhang et al, 2017). In a rat model of acute transient cerebral ischemia, Sac-1004 reduced BBB leakage and loss of tight junction proteins, inhibited glial activation, and ameliorated neurological deficits and ischemic damage (Zhang et al, 2017).…”
Section: Emerging Pharmacological Approachesmentioning
confidence: 99%
“…However, Borlongan et al () demonstrated that, in a rat model of MCAO for 1 hr, intravenously injected hMSCs (human umbilical cord blood cells), which were injected with BBB permeabilizer (mannitol) during the occlusion of MCA, were not found in the damaged brain parenchyma at 3 days after ischemia (Borlongan et al, ). Regarding the degree of damage of ischemic areas after ischemic insults, it has been reported that 1 hr of transient focal cerebral ischemia did not induce coagulation necrosis in the ischemic area at immediate phase after ischemia (Garcia, Yoshida, Chen, et al, ), but, severe infarction is shown 1–4 days after 1 h of transient focal ischemia (Zhang, Park, Maharjan, et al, ). Furthermore, early BBB leakage is differently detected depending on molecular weight of used tracers, namely, plasma IgG (~150 kDa) is detected within 3 hr and fluorescein isothiocyanate‐dextran (2,000 kDa) within 1 day after focal ischemia (Shi, Zhang, Pu, et al, ), indicating that a larger molecular weight of tracer could be extravasated after severe infarction.…”
Section: Discussionmentioning
confidence: 99%
“…I/R was induced by middle cerebral artery occlusion on the left side as previously described in Zhang et al . (24). Briefly, the left common carotid artery (CCA) was exposed and separated from the vagus nerve.…”
Section: Methodsmentioning
confidence: 99%
“…(24) with slight modification. Briefly, after 16 h reperfusion, EB (2% in 0.9% saline, 4 ml/kg) was injected into the tail vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation